Individual and Collective Dimensions of Resilience Within Political Violence. (July 2013) - Sousa, Cindy A.; Haj-Yahia, Muhammad M.; Feldman, Guy; Lee, Jessica
Research has documented a link between political violence and the functioning of individuals and communities. Yet, despite the hardships that political violence creates, evidence suggests remarkable fortitude and resilience within both individuals and communities. Individual characteristics that appear to build resilience against political violence include demographic factors such as gender and age, and internal resources, such as hope, optimism, determination, and religious convictions. Research has also documented the protective influence of individuals' connection to community and their involvement in work, school, or political action. Additionally, research on political violence and resilience has increasingly focused on communities themselves as a unit of analysis. Community resilience, like individual resilience, is a process supported by various traits, capacities, and emotional orientations toward hardship. This review addresses various findings related to both individual and community resilience within political violence and offers recommendations for research, practice, and policy.